Sistem Pakar Diagnosa Penyakit Kulit pada Manusia dengan Metode Cased Based Reasoning (CBR) - Baco, Syarifuddin; Rosmiati, Rosmiati; Maulana, Muh Irzan (Patria Artha Technological Journal, 2021)
Skin Care Clinic Laser Therapy located at Jl. Ali Malaka No.15, Maloku, Kec. Makassar, Makassar City, South Sulawesi, Indonesia, in addition to serving skin care consultations also performs a series of diagnoses of symptoms on the skin but limited in serving customers, especially during the current COVID-19 pandemic so that there are obstacles that cause difficulty in consulting diseases but can be overcome by technological advances. At this time the development of technology has been very rapid, not only in the field of information, industry, but in the field of medicine. Implementation that can be applied in the field of medicine, one of which is the system of experts in the diagnosis of skin diseases by using case-based reasoning (CBR) method in the ability of expert knowledge so as to facilitate patients to see the initial diagnosis and provide response (answer) in the form of solutions to problems that occur.